Parental leave policies and parents' employment and leave-taking - Wen-Jui Han; Christopher J. Ruhm; Jane Waldfogel (Institute for the Study of Labor (IZA), 2007)
Utilizing data from the June Current Population Survey (CPS) Fertility Supplement merged with data from other months of the CPS, we describe trends in parents' employment and leave-taking after birth of a newborn and analyze the extent to which these behaviors are associated with parental leave policies. The period we examine - 1987 to 2004 - is one in which such policies were expanded at both the state and federal level. We also provide the first comprehensive evidence as to how these expansions are correlated with employment and leave-taking for both mothers and fathers over this period. Our main finding is that leave expansions have increased the amount of time that new mothers and fathers spend on leave, with effects that are small in absolute terms but large relative to the baseline for men and much greater for college-educated women than for their counterparts with less schooling.
Keywords: J13; 330; Parental leave policies; parental employment; leave-taking; Eltern; Beschäftigung; Familienpolitik; Erziehungsurlaub; Lohnersatzleistungen; Väter; Mütter; USA